Strategic Management Accounting: A Case Study Evaluating its Presence and Usage in Practice - Lim, Song Yia (2013)
This paper investigates the presence of Strategic Management Accounting (SMA) in the IT shared Services that belong to global organisation delivering fast moving consumer goods. It seek to establish whether SMA is practiced in the real world as many prior researches have provided mixed conclusions on the usage of SMA by practitioners. The case study approach allowed the paper to have detailed in-sight on what management accounting practices was adopted in the case organisation. The result of the research found many characteristics of SMA in the case company which is widely utilised for strategic decision making/planning and management control. In addition, the paper found that SMA adopts a contingent approach because the usage of SMA is dependent on situational factors or contingent factors that vary from organisation to organisation. However, further exploration, the paper found that SMA has the risk of introducing additional administrative effort to the organisation by introducing new processes for data collection. It also found that SMA has extended the role of management accountant to a strategic player. All in all, it concludes that SMA is used by practitioners given that the key characteristics of SMA were clearly identifiable in the case company.